Application of Prefabricated Vertical Drain in Soil Improvement - Tedjakusuma B. (Civil Engineering Dimension, 2012)
Although the use of Prefabricated Vertical Drain (PVD) in soil improvement is not new, this paper is interesting since it gives the full spectrum from preliminary design stage; trial embankment and pilot test to final soil improvement. The final installation of the PVD was based on the soil investigation report and the results of instrumentation monitoring. Finally, using back analysis, vertical and horizontal coefficients of consolidation and compression index can be determined, which can be applied to predict a more accurate prediction of settlement.